Floating-body effect in partially/dynamically/fully depleted DG/SOI MOSFETs based on unified regional modeling of surface and body potentials - Chiah, Siau Ben (2014)
A compact terminal current/charge model for partially/dynamically/fully depleted (PD)/(DD)/(FD) double-gate (DG) and silicon-on-insulator (SOI) MOSFETs with floating-body (FB) effect based on unified regional modeling of the surface and body potentials is presented. The model accurately describes the physical behavior of the impact-ionization current that gives rise to the hump in the C-Vcharacteristics and the body thickness- and doping-dependent kink effect. The FB potential at the zero-field location in the body is the key to model the electrical characteristics of PD/DD/FD devices with complete body doping and thickness scalability. The model is validated by comparison with I-V C-V data of the numerical devices in a given range of body doping, body thickness, and temperature. Such a scalable model is important for physical and variability modeling of DG/SOI FinFETs with doped body.